Aging and factors associated with quality of life for elderly people in State of Mexico - Soria-Romero, Zuriel; Montoya-Arce, Bernardino Jaciel (Papeles de Población; Vol. 23 Núm. 93 (2017): Papeles de Población, 2017)
This article presents an analysis of the relationship between socio-demographic, economic and health conditions with the quality of life of elderly who participated in the Survey on Demographic Aging in the State of Mexico. Using the technique of Principal Component Analysis, an index of quality of life considering objective and subjective variables grouped into four areas: well-being, income, housing conditions and health conditions was calculated. From the analysis it emerged that more than half of the study population lacks adequate conditions that affect their quality of life and shows that the factors that greatly related to the quality of life of elderly are the level of schooling, marital status and rightfulness condition.